2017
DOI: 10.21272/sec.1(3).98-115.2017
|View full text |Cite
|
Sign up to set email alerts
|

Creating Enhanced Capacity for Local Economic Development (LED) through Collaborative Governance in South Africa

Abstract: The complexities of the twenty-first century have paved way for the emergence and proliferation of cross boundary collaboration in the lexicon of localised and territorial development. Collaborative governance is increasingly playing a vital role in addressing the multi-dimensional challenges of the contemporary era. This paper seeks to contextualise collaborative governance as a possible remedy that could help to salvage the incapacitated municipalities and be more resourceful in their developmental mandate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In the XXI century their importance constantly increases with the adoptions of the society to the challenges of new technological order. They demonstrate the main ideas of regional systems economic and social changes [4]. According to modern scientific assessments globalization is one of the main megatrends, accompanied by globally increasing economic integration [5].…”
Section: Localization Of Regional Resources Within the Strategy Formimentioning
confidence: 89%
“…In the XXI century their importance constantly increases with the adoptions of the society to the challenges of new technological order. They demonstrate the main ideas of regional systems economic and social changes [4]. According to modern scientific assessments globalization is one of the main megatrends, accompanied by globally increasing economic integration [5].…”
Section: Localization Of Regional Resources Within the Strategy Formimentioning
confidence: 89%
“…Ansell and Gash pointed out a series of factors for successful collaboration, namely face-to-face dialogue, trust building, the development of commitment and shared understanding [49]. Kamara argued that collective governance is still in its infancy in South Africa [13]. Leck and Simon [14] showed that maximum effectiveness of local government initiatives can only be achieved when collaborative governance includes all complementary skills and resources from all relevant private, local, regional and national institutions.…”
Section: Literature On Public Participation and Collaborative Governancementioning
confidence: 99%
“…When drawing on the literature of collaborative governance [13,14,49], maximum effectiveness in the implementation of the EDAS approach can only be achieved if the approach is formalised within a local government; therefore, it should form part of the local government's policies and should include clear roles and responsibilities for all stakeholders, whether private, local, regional or national.…”
Section: The Approach Must Be Formalised With Clear Institutional Arrmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries, LED is considered as a solution to unemployment, poverty, and income inequality. This is because LED is an active process that envisages a mutual relationship between local communities, local authorities and other relevant stakeholders so as to create local development that is sustainable (Kamara, 2017).…”
Section: Introductionmentioning
confidence: 99%